THE DIFFERENCE BETWEEN INDIVIDUALS DOING SPORTS OR NOT IN TERMS OF THEIR STRESS COPING STYLES - TAZEGÜL, Ünsal (IJRDO- Journal of Educational Research, 2016)
In this study, it was aimed to analyze the difference between individuals doing sports or not in terms of their stress coping styles. The target population of the study was created by the students of Istanbul Gelişim University while the sample of the study was selected by a total of 121 students, 60 of them doing regularly sports and 61 of those not doing sports, who voluntarily agreed to participate in the study. Stress coping styles of students have been measured through Coping Styles of Stress Scale that was adapted in Turkish by Şahin and Durak. “The Kolmogorov-Smirnov Test” was applied in order to decide whether data has normal distribution and “Levene’s Test” was applied to test the homogeneity of variances and it is observed that data is homogeneous and has a normal distribution. Descriptive statistics and one-sample t test was used to analyze the data. At the end of the study, it was determined that individuals doing sports’ scores related to self-confidence and optimistic approach were higher than those not doing sports. In addition, individuals not doing sports’ scores related to submission and obedience were observed as higher than individuals doing sports.